A "rational" Homer: some aspects of poetic reform in Melchiorre Cesarotti's translation of the "Iliad" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2025)
This paper aims to highlight some translational and theoretical aspects of the monumental (and still little explored) work carried out by Melchiorre Cesarotti on Homer’s Iliad. Beyond his rewriting of La Morte di Ettore (1795), this work resulted in two editions of the poem (Penada 1786-1794 and Brandolese 1798-1802, both in ten volumes), which include a preliminary Ragionamento, an exceptional set of notes, and two different translations: one literal in prose and one unfaithful in verse, aimed at restoring the Iliad that Homer would have written if he had lived in the XVIIIth century. The article provides an overview of the main reformist tendencies that shaped this poetic version, with a focus on the interventions driven by rationalism. Specifically, it examines linguistic adjustments (such as the rejection of archaic stylistic features in the Homeric language), as well as poetic (the question of verisimilitude and the “mirabile”) and rhetorical considerations (particularly in the translation of similes).
Keywords: Melchiorre Cesarotti; Homer; Iliad; Literary translation; Translation studies; Querelle des Anciens et des Modernes; 18th century; Elinghtenment